Sustainable waste management strategy based on circular economy in Pangkalpinang City - Susanti, Lisma Dwi; Reniati, Reniati; Altin, Darus (Studi Ekonomi dan Kebijakan Publik, 2025)
Purpose: This study aimed to formulate a circular economy-based waste management strategy to support the achievement of Sustainable Development Goals (SDGs) in Pangkalpinang City. Research Methodology: This study employs a descriptive quantitative approach using the Analytic Hierarchy Process (AHP). It involves 15 stakeholders from the Pentahelix sectors (government, business actors, academics, community organizations, and media) to evaluate five criteria—government policy, infrastructure, community participation, recycling technology, and economic impact— and five strategic alternatives: enhancing recycling facilities, environmental education, strengthening regulations, implementing automation technology, and providing economic incentives. Results: The analysis revealed that strengthening government regulations (weight: 1.469) is the top strategic priority, highlighting the central role of policy and enforcement in sustainable waste management. This is followed by enhancing recycling facilities (0.901) and implementing automation technologies (0.899). Among the criteria, community participation was the most influential factor (27.01%), underscoring the importance of public involvement in sorting, recycling, and reducing waste generation. Conclusions: An integrated circular economy-based strategy emphasizing regulatory reinforcement and active community participation is essential for sustainable urban waste management in Pangkalpinang. Limitations: This study is limited to stakeholders within Pangkalpinang City and excludes broader regional perspectives and behavioral aspects of the wider population. Contribution: This study provides a practical framework for policymakers and stakeholders to design multisectoral waste management strategies that balance environmental, social, and economic dimensions, thereby aligning local practices with SDGs.